2006
DOI: 10.1007/s00442-005-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature and host availability on the host exploitation strategies of sexual and asexual parasitic wasps of the same species

Abstract: In the hymenopteran parasitoid Venturia canescens, asexual (obligate thelytoky not induced by Wolbachia bacteria) and sexual (arrhenotokous) wasps coexist in field conditions despite the demographic cost incurred due to the production of males by sexual females. Arrhenotoky predominates in field conditions, whereas populations in indoor conditions (mills, granaries) are exclusively thelytokous. These differences in the relative abundance of the two modes of reproduction between environments suggest that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 55 publications
(63 reference statements)
5
42
0
1
Order By: Relevance
“…Therefore, we cannot claim that the differences found are a general feature of the two reproductive modes. However, previous results showing (1) consistent differences between the two modes of reproduction in line with adaptive considerations (Li et al 2003;Amat et al 2006;Thiel et al 2006) and (2) a lack of influence of geographical location Thiel et al 2006), strengthen the findings of this work.…”
Section: Differential Energy Allocation As An Adaptation To Habitatsupporting
confidence: 88%
“…Therefore, we cannot claim that the differences found are a general feature of the two reproductive modes. However, previous results showing (1) consistent differences between the two modes of reproduction in line with adaptive considerations (Li et al 2003;Amat et al 2006;Thiel et al 2006) and (2) a lack of influence of geographical location Thiel et al 2006), strengthen the findings of this work.…”
Section: Differential Energy Allocation As An Adaptation To Habitatsupporting
confidence: 88%
“…Ardeh et al (2005a, b) found no differences between arrhenotokous and thelytokous Eretmocerus mundus Mercet (Hymenoptera: Aphelinidae) with respect to host discrimination. Amat et al (2006) saw no differences in the oviposition behaviors of arrhenotokous and thelytokous Venturia canescens Gravenhorst (Hymenoptera: Ichneumonidae), although arrhenotokous females exhibited longer patch residence times. Subsequently, Amat et al (2009) found similar responses by both populations to parasitized hosts, but thelytokous females adjusted their patch residence time by using cues from conspecifics while arrhenotokous wasps did not.…”
Section: Introductionmentioning
confidence: 81%
“…Recent studies on V. canescens appear to demonstrate niche differentiation that could explain the coexistence of the two reproductive modes, i.e. thelytokous individuals seem to be more adapted to anthropogenic and arrhenotokous individuals to natural habitats (Amat et al, 2006(Amat et al, , 2009Thiel et al, 2006;Pelosse et al, 2007Pelosse et al, , 2010Foray et al, 2011). Future studies should investigate the genetic basis of thelytoky in V. canescens since thelytoky in the parasitoid wasp Lysiphlebus fabarum (Hymenoptera: Braconidae) is determined by a single recessive gene (Engelstädter et al, 2011;Sandrock & Vorburger, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A key point of contention is in the imbalance between the obvious demographic and genetic costs of sex (Maynard-Smith, 1978) vs the lack of demonstrated short term advantages. Niche differentiation, highlighted by environmental dependent differences in fitness of sexual and asexual forms, seems to be a fruitful avenue of investigation to resolve this issue (Amat et al, 2006(Amat et al, , 2009Tobler & Schlupp, 2010). In order to evaluate this hypothesis, it is necessary to compare closely related sexual and asexual species or individuals of the same species that occur sympatrically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation